The Impact of YouTube Content on Toddler Behaviour: A Study on Parental Awareness and Demographic Influences - Suneesh K S, Padmanabhan T, Poovarasan G, Jeeva V (South Eastern European Journal of Public Health, 2025)
In this modern world, technology has become a significant feature that is part of every human’s life. Besides, third-millennium kids are born with technology and an enormous chance for easy access. It causes the behaviour of every kid who facilitates to access technology like watching TV, Internet, and mobile phones at an early stage. In consideration, this study examines the correlation between YouTube content and the impact on toddlers.Structured questionnaires are developed based on existing literature to assess parental awareness, the impact of demographic factors such as economic status, residence, and family structure on toddlers' viewing hours, and the effects of viewing content on toddlers, including alterations in aggressive behaviour, imitation, and sleep deprivation.More than 300 samples are obtained using snowball sampling procedures, and the acquired data is subjected to statistical analysis to determine the specified correlation. This survey indicates that despite parents being informed about the repercussions of improper content on YouTube, they have yet to act, resulting in the majority of toddlers using YouTube instead of YouTube Kids. The results also indicate that demographic factors significantly affect toddlers' usage time, with more YouTube exposure correlating with heightened aggression, sleep deprivation, and imitation in toddlers.